ETHNIC ASPECTS OF SOCIAL INTERACTION IN THE MEGACITY (CASE STUDY MOSCOW) - M. I. Seredina (Real Economics Publishing House, 2014)
The article considers ethnic aspects of social interaction in Russia's largest megacity - Moscow. The features of the formation of ethnic communities (groups) are analyzed at different stages of the city development. It is emphasized the interaction tools of ethnic communities. It is analyzed the issues of reducing ethnic conflicts and using the experience of positive cooperation of various national groups in Moscow.